Contamination by antibiotic-resistant bacteria in foods: the danger of eating ready-to-eat vegetables (Research, Society and Development, 2022)
Introduction: The heavy tendencie to purchase ready for consumption vegetables in the last years, has been significantly assossiated to infection outbreaks and food poisoning.  These ingredients are potentially contamined by pathogenic microorganisms and the greatest concern refers to human exposition to resistant antimicrobial agents, which encoraged the researchers to study many forms of resistant strains in food. Objective: The purpose of this study was to elucidate the contamination of ready for consumption vegetables with antibiotic resistant bacteria and the risks of its consumption. Methodology: It's a narrative review on existing literature that aimed to clarify the risks of ingestion of ready for consumption vegetables due to its contamination with antibiotic resistant bacteria. The research was made through online access to the following database: Google Scholar, National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Biblioteca Virtual em Saúde (BVS). Results and discussion: In all of the 25 articles researched, resistant bacteria were found. Of the total, 86,51% of the bacteria were resistan to at least one antibiotic. Of the bacteria which showed resistance, 76,92 % were resistant to at least 5 antibiotics and 44,23% were resistant to over 10 antibiotics. Conclusion: The present study demonstrates that ready for consumption vegetables have a large microbiota with different genus of bacteria, the majoritt of which antibiotic resistant.